PENGARUH WAKTU KERJA PADA KELELAHAN KERJA TERHADAP SUPIR TRANSPORTASI DARAT B3 - Rizki Alya Harahap; Susilawati (CV. ADIBA AISHA AMIRA, 2024)
Work fatigue is a common problem among B3 ground transportation drivers which can have a negative impact on their health and performance. One of the factors that can affect the level of work fatigue is long working hours. This study aims to identify and analyze the effect of working time on work fatigue in B3 ground transportation drivers. This study used a survey research method and data collection was carried out through questionnaires distributed to B3 ground transportation drivers who are actively working in several transportation companies. The questionnaire collects information about the characteristics of the respondents, working time, and the level of fatigue experienced by the driver.